2008
DOI: 10.1007/s11547-008-0334-x
|View full text |Cite
|
Sign up to set email alerts
|

Poly-L-lactic acid — hydroxyapatite (PLLA-HA) bioabsorbable interference screws for tibial graft fixation in anterior cruciate ligament (ACL) reconstruction surgery: MR evaluation of osteointegration and degradation features

Abstract: BioRCI-HA screws allow adequate primary stability and superior osteoconduction and biocompatibility in comparison with plain PLLA screws. The absence of ferromagnetic artefacts allows accurate MRI follow-up and adequate evaluation of ligament synovialisation, screw degradation and graft osteointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…With 54% follow-up, the authors found that all of the Biosteon interference screws (Stryker, Mahwah, New Jersey), composed of hydroxyapatite-PLLA, had been resorbed and density in the screw tracks was comparable with that in the surrounding bone. Macarini et al evaluated thirty-one patients using MRI over a forty-month period after surgery 24 . The authors found evidence of edema and cyst formation in a group of fifteen patients ten to thirteen months after implantation of hydroxyapatite-PLLA interference screws, but this resolved over time and was absent, having been replaced by fibrous tissue, on repeat MRI scans in a separate group of sixteen patients thirty to forty months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With 54% follow-up, the authors found that all of the Biosteon interference screws (Stryker, Mahwah, New Jersey), composed of hydroxyapatite-PLLA, had been resorbed and density in the screw tracks was comparable with that in the surrounding bone. Macarini et al evaluated thirty-one patients using MRI over a forty-month period after surgery 24 . The authors found evidence of edema and cyst formation in a group of fifteen patients ten to thirteen months after implantation of hydroxyapatite-PLLA interference screws, but this resolved over time and was absent, having been replaced by fibrous tissue, on repeat MRI scans in a separate group of sixteen patients thirty to forty months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one study completed a 10-year follow-up and found that all patients had an osseous cyst in the place of the degraded screws as observed with MRI (Warden et al 2008). To address the problem of osteointegration, biocomposite materials, composed of polyesters combined with ceramic particles (typically tricalcium phosphate [TCP] or hydroxyapatite), have been recently introduced (Macarini et al 2008;Tecklenburg et al 2006;Hunt and Callaghan 2008;LeGeros 2002;Tay et al 1999;Lu et al 2009). However, their effectiveness in terms of osteointegration has been promising but inconclusive (Warden et al 2008;Barber and Dockery 2008), and breakage during implantation still remains a significant problem for these polymer-based materials (Tecklenburg et al 2006).…”
Section: Need For Novel Biomaterials and Devicesmentioning
confidence: 99%
“…Degradation kinetics differ substantially among different bioabsorbable polymers and numerous factors affect degradation rates, including molecular weight, sterilization, implant size, self-reinforcement, copolymer or stereocopolymer ratios, and processing techniques [2]. Postoperative radiographic evaluation of early generation poly-L-lactic acid (PLLA), polyglycolide and poly-D,L-lactide-co-glycolide screws revealed slow resorption rates and minimal, if any, osteoconductivity, despite good to excellent clinical results [3][4][5][6][7][8][9][10][11]. The addition of β-tricalcium phosphate (βTP) or hydroxyapatite (HA) helps buffer PLLA acidic breakdown providing a scaffold for bony ingrowth [12,13].…”
Section: Introductionmentioning
confidence: 99%